2012
DOI: 10.1007/s10620-012-2130-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in Adults with Inflammatory Bowel Disease: Potential Role of Ethnicity

Abstract: A significantly higher percentage of South Asians had hypovitaminosis D when compared to Caucasians. Disease severity trended towards an inverse relationship with vitamin D status in all South Asian and Caucasian CD patients, although most patients in this study had only mild to moderate disease. We suggest that vitamin D supplementation should be considered in all adult IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Previous studies have reported a high incidence of vitamin D deficiency in patients with IBD (9)(10)(11)31). In Crohn disease, several groups have demonstrated an association between vitamin D and clinical disease activity (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a high incidence of vitamin D deficiency in patients with IBD (9)(10)(11)31). In Crohn disease, several groups have demonstrated an association between vitamin D and clinical disease activity (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Northern Hemisphere populations that reside at higher latitudes where daily sunlight exposure is lower have a higher prevalence of IBD, particularly Crohn disease (4,5). Previous analyses have also reported a high prevalence of vitamin D deficiency in patients with both Crohn disease and UC (6)(7)(8)(9)(10)(11). Furthermore, several studies have demonstrated an inverse correlation between clinical symptoms and serum vitamin concentrations in patients with Crohn disease (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…It included 14 studies with a total of 1,891 patients and reported that patients with IBD had 64% higher odds of vitamin D deficiency when compared with controls [15]. An association with disease activity has been described more inconsistently, with some authors arguing that there is a relation between lower levels of vitamin D and higher disease activity [6,[16][17][18][19][20][21], while others have not found any relation [22][23][24]. There are 2 published Portuguese studies on this subject, both from the north of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, increasing 25(OH)D levels through high-dose vitamin D supplementation may have therapeutic potential and prevent relapse in CD (17,18) , although this still warrants confirmation in controlled trials. Several studies have been conducted to demonstrate a correlation between vitamin D status and inflammatory bowel disease activity (6,14) . However, few studies (33) have so far hypothesized that vitamin D deficiency is associated with a lower quality of life (QOL) in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%